Morality Issues in The Islamic Criminal Law and The Indonesian Criminal Code Draft under The Perspective of Maqasid Al-Shari’ah - Sanuri, Sanuri (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2021)
This is a bibliographical research to highlight the moral issues in the Islamic Criminal Law and the Indonesian Criminal Code Draft, such as pornography, acts of adultery, cohabiting, prevention of pregnancy and abortion, and rape on the perspective of maqasid al-shari’ah”. The intersection between the principles of the Islamic Criminal Law and those of the Criminal Code Draft in Indonesia can be seen from a transformative relationship occurs substantively and contextually through the five features in daruriyyat al-khamsah of the theory of maqasid al-shari’ah. In addition, the transformation of the two legal systems can also be measured through the three basic concepts that exist in the Islamic Criminal Law namely zawajir (repressive), jawabir (preventive), and ta’dib (educative) while still pays attention to the universal values such as justice (al-‘adalah), freedom (al-hurriyyah), equality (al-musawah), wisdom (al-hikmah), and human kindness (masalih al-‘ibad).